2005
DOI: 10.1073/pnas.0503326102
|View full text |Cite
|
Sign up to set email alerts
|

Essential role for Gα 13 in endothelial cells during embryonic development

Abstract: Toward identifying the roles of protease-activated receptor-1 (PAR1) and other G protein-coupled receptors important for vascular development, we investigated the role of G␣ 13 in endothelial cells in the mouse embryo. LacZ inserted into G␣13 exon 1 was highly expressed in endothelial cells at midgestation. Endothelialspecific G␣13 knockout embryos died at embryonic days 9.5-11.5 and resembled the PAR1 knockout. Restoration of G␣ 13 expression in endothelial cells by use of a Tie2 promoter-driven G␣13 transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
83
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 37 publications
2
83
0
1
Order By: Relevance
“…In addition to the study noted above demonstrating a role for G 12 proteins in breast cancer metastasis (30), reports have appeared suggesting a role for these proteins in neutrophil (25) and fibroblast migration (50). Further, studies on the role of G 12 signaling in development have suggested that genetic ablation of the G 12 proteins results in impaired cell migration (21)(22)(23)(24). Interestingly, some of these studies that were conducted in Drosophila and zebrafish, revealed that signaling through the G 12 family is required for the cell shape changes and movements required for normal gastrulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the study noted above demonstrating a role for G 12 proteins in breast cancer metastasis (30), reports have appeared suggesting a role for these proteins in neutrophil (25) and fibroblast migration (50). Further, studies on the role of G 12 signaling in development have suggested that genetic ablation of the G 12 proteins results in impaired cell migration (21)(22)(23)(24). Interestingly, some of these studies that were conducted in Drosophila and zebrafish, revealed that signaling through the G 12 family is required for the cell shape changes and movements required for normal gastrulation.…”
Section: Discussionmentioning
confidence: 99%
“…G 12 Signaling Promotes Prostate Cancer Cell Invasion-Since previous studies have suggested a role for the G 12 proteins in cell migration (21)(22)(23)(24)(25) and cancer cell invasion (30), we next examined the role of G 12 signaling in prostate cancer cell invasion. We found that expression of the activated forms of G␣ 12 or G␣ 13 in the PC3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, G␣ 12 Ϫ/Ϫ mice appear viable and grow normally. In addition, during vascular development, a selective and critical role for G␣ 13 in endothelial cells has been demonstrated (55). It therefore appears that G␣ 13 plays a significant role in PAR1-induced developmental processes.…”
Section: Discussionmentioning
confidence: 99%
“…The Nsd1 (M.m.168965) belongs to an emerging family of proteins, Nsd1is a developmental regulatory protein that is essential for early post-implantation development [24]. Gna13 (M.m.193925) plays an important role in embryonic vascular development as a candidate mediator of protease-activated receptor-1 (PAR1) signaling [25]. Architectural chromatin protein HMGA2 (M.m.157190) is highly expressed in male meiotic cells.…”
mentioning
confidence: 99%